ANALYSIS OF DONOR POTENTIAL OF GENERAL INTENSIVE CARE UNIT: THE PROBLEMS AND PERSPECTIVES OF ITS USE - P. Y. Filiptsev; Y. Y. Romanovsky; R. B. Akhmetshin (Вестник трансплантологии и искусственных органов)
There were studied the use of donor pool in intensive care unit (ICU) at Moscow Clinical Hospital No 7 as a typical general ICU during the period of 2005–2008. If ICU receives the number of patients a year, equal to 1500–1700, mortality rate is 30% (463–532 died per year). Nevertheless, the actual percentage of potential donors is 5,8–8,6%. Thus, patients dying in ICU during the first 24 hours represent additional opportunities to increase the donor pool. The real way to improve the situation should be considered an introduction of transplant coordinators into hospital staff.